Design and Development of a Remotely Operated Underwater Vehicle (ROV) - Satiamurti, Thineshwaran; Abdul Kadir, Herdawatie (Evolution in Electrical and Electronic Engineering, 2024)
This work overcomes obstacles in traditional underwater exploration by creating a cutting-edge Remotely Operated Underwater Vehicle (ROV). Research in this field is captivating and holds immense potential. However, underwater activities challenges and hazardous conditions limit human involvement in these environments. Thus, there is a need for underwater exploration vehicles to the point humans cannot reach, including recording underwater data. The current underwater vehicles have notable constraints, limiting their capabilities and resulting in uninformed decision-making and costly errors due to the lack of real-time data transmission capabilities. The proposed ROV, featuring an open frame structure and microcontroller ESP8266, integrates advanced components such as the ESP32-Cam, IMU-MPU6050 sensor, depth sensor, and T200 Blue Robotic thrusters. The methodology includes comprehensive block diagrams detailing the overall remote system and the proposed design. The results demonstrate a finalized structure design, mechanical design arrangements, and ROV server connection. An optimized ROV structure with extensive functionality, connectivity, and reliability testing demonstrates ideal buoyancy, balance, and waterproofing capabilities. Incorporating a user-friendly Blynk app interface and seamless integration with ThingSpeak enhances real-time data monitoring. This innovative ROV work contributes to society by overcoming challenges in traditional underwater exploration.